Examining the Current Status of International Education Standards Compliance in ASEAN Countries (Journal of Business Management and Accounting, 2017)
This study examined the IES compliance behaviour of IFAC members from the Association of South East Asian Nations (ASEAN) countries after ten years of International Education Standards (IES) implementation. The content analysis approach was employed. Data were collected from IFAC’s Member Compliance Program and websites of member bodies from ASEAN countries. Findings show that only three out of ten IFAC member bodies from ASEAN fully complied with the pre-qualifications standards of accounting education programme. Noncompliance are mainly in the content of accounting education programme specifically IT competences in IES 2 and the mentoring aspects in IES 5. This study recommends sustainable monitoring and supervision of IES implementation and compliance to achieve the intended IFAC IES objectives. Collaborative arrangements between universities regarding capacity building for academic staff, implementation of adequate accounting curricula and potentially joint degree programs could be put in place to push for IES full compliance among ASEAN countries to reduce regional accounting education differences while encouraging accountants’ mobility within the region